Influence of timeliness and receipt of first treatment on geographic variation in non‐small cell lung cancer mortality. Issue 8 (21st October 2020) - Wah, Win; Stirling, Rob G.; Ahern, Susannah; Earnest, Arul
Abstract: Mortality from non‐small cell lung cancer (NSCLC) exhibits substantial geographical disparities. However, there is little evidence on whether this variation could be attributed to patients' clinical characteristics and/or socioeconomic inequalities. This study evaluated the independent and relative contribution of the individual‐ and area‐level risk factors on geographic variation in 2‐year all‐cause mortality among NSCLC patients. In the Hierarchical‐related regression approach, we used the Bayesian spatial multilevel logistic regression model to combine individual‐ and area‐level predictors with outcomes while accounting for geographically structured and unstructured correlation. Individual‐level data included 3330 NSCLC cases reported to the Victoria Lung Cancer Registry between 2011 and 2016. Area‐level data comprised socioeconomic disadvantage, remoteness and pollution data at the postal area level in Victoria, Australia. With the inclusion of significant individual‐ and area‐level risk factors, timely (≤14 days) first definitive treatment (odds ratio [OR] = 0.73, 95% credible interval [Crl] = 0.56‐0.94) and multidisciplinary meetings (MDM) (OR = 0.74, 95% Crl = 0.59‐0.93) showed an independent association with a lower likelihood of NSCLC 2‐year all‐cause mortality. Timely and delayed (>14 days) first nondefinitive treatment, no treatment, advanced clinical stage, smoking, poor performance status, public hospital insurance and area‐level deprivation were independently associated with a higher likelihood of 2‐ and 5‐year all‐cause mortality. NSCLC's 2‐year all‐cause mortality exhibited substantial geographic variation, mainly associated with timeliness and receipt of first definitive treatment, no treatment followed by patient prognostic factors with some contribution from area‐level deprivation, MDM and public hospital insurance. This study highlights NSCLC patients should receive the first definitive treatment within the recommended 14‐days from diagnosis. Abstract : What's new? Mortality from non‐small cell lung cancer (NSCLC) exhibits substantial geographical disparities. However, whether this variation is attributable to patients' clinical characteristics and/or socio‐economic inequalities remains unclear. This Bayesian spatial multi‐level model combines individual‐ and area‐level predictors with outcomes while accounting for geographically‐structured and unstructured correlation. Timely first definitive treatment and multidisciplinary meetings are associated with lower two‐year mortality. Timely and delayed first non‐definitive treatment, no treatment, advanced clinical stage, ever smoking, poor performance status, public hospital, and area‐level deprivation are associated with higher two‐ and five‐year mortality. NSCLC patients should receive first definitive treatment within the recommended 14 days.